Knowledge and concerns about HIV/AIDS among childbearing women in Mahalapye, Botswana - Lebodi, Pamela (My University, 2014)
The aim o f the study w as to determ ine the know ledge and concerns about HIV/AIDS among childbearing w om en in M ahalapye, Botswana. A descriptive study design using an inri-view schedule was used. The sam ple o f 166 respondents (aged 18-29 years) w as draw n from a population o f w om en w ho attended M ahalapye clinics. D ata w ere analysed by use o f a com puter and descriptive statistics including frequencies and percentages. The dem ographic data showed that the m ajority (85.5%) o f the respondents w ere not m arried, o f w hom 78% had partners and 9% w ere cohabiting. Seventy percent had secondary education and 70.4% w ere unem ployed, hence their dependence on their partners and relatives for econom ic support. The results show ed that the respondents had a high level o f know ledge about HIV/AIDS including risk factors, m ode o f transm ission and prevention. A ll respondents (100%) seem to be aware that a person can contract H IV through having m ultiple sexual partners. The m ajority (98%) stated that H IV can be transm itted sexually and 97% said that infected pregnant w om en can transm it H IV to their babies. N inety seven percent o f w om en said that the spread o f H IV can be prevented by \ h g condom s, 21.1 % said by having sex less frequently and 98.8% said people can protect them selves from contracting H IV by through sharing utensils and food w ith an infected person, 38% believed that mosquitoes and insects can transm it H IV and 41.6% did not believe that a person infected with HIV m ight look healthy. Thirty six (21.7% ) w om en perceived them selves not to be at risk o f H IV ow ing to current m onogam ous relationships and their trust in their partners. Radio and health personnel w ere m entioned as the m ain sources o f inform ation about HIV/AIDS. All (100% ) respondents revealed that they w ere afraid o f becom ing infected w ith the virus and 98.2% said that they w ere concerned that m en do not like using condom s. Even though 93.4% said that they w ere free to discuss sexual activities w ith their partners, 83.7% said that they w ould not find it easy to reveal their H IV status to their partner for fear o f rejection and stigm atisation. The results show ed that know ledge was related to education level. A ll w om en w ho had post secondary education indicated that AIDS cannot be cured by consulting traditional doctors ( 9 -0 0v'7) and W estern doctors (p=0.046) as com pared w ith those w ho did /iOf hav-'-post secondary education. A ge and m arital status seem not to be related to know ledge (p>0.05). Educational program m es targeted at these w om en should address the m isconceptions about the m ode o f transm ission. W om en should be equipped w ith effective com m unication and decision m aking skills that w ill em power them to adopt behaviours that will protect them from becom ing infected or infecting others. Further research is needed to determ ine the extent to w hich concerns expressed by w om en in this study are expressed by other groups o f women.
Keywords: Acquired Immunodeficiency Syndrome--prevention & control